Analisis Risiko Rantai Pasok Material dalam Pelaksanaan Proyek Konstruksi Gedung Di Aceh - Hayati, Kemala; Citra , Keumala; Soviana, Widya; Farhan, Rizki (Tameh, 2022)
The material supply chain is a material distribution flow that varies from various sources or suppliers, until the material arrives at the project site. This study aimed to analyze material supply chain risk factors that arise in the implementation of building construction projects in Aceh Province, as well as identify solutions to prevent material supply chain risk factors that arise in the implementation of building construction projects in Aceh Province. The methods developed in this research are validity test, reliability test, quantitative descriptive, and multiple regression analysis through SPSS software version 25. From the validity test results obtained, the value of Rcount ≥ Rtable. This shows that the validity test performed on all questions is valid. Furthermore, the results of the reliability test obtained the average value of each variable of 0.708, then the reliability test was said to be reliable. Because the value of a variable is said to be reliable (reliable) if Cronbach Alpha value exceeds 0.6. Then from the results of the descriptive analysis, there are indicators that are often questioned as risk factors, namely the delay of the main contractor in paying subcontractors (X2.8) with a mean value of 3.39. This shows that the majority of respondents stated that X2.8 has a high influence on the occurrence of material supply chains in the implementation of construction projects. From the results of the correlation analysis, the R value of 0.382 (low/weak), then the two variables have a unidirectional relationship. This means that if the value of the X variable is high, then the value of the Y variable will also be high or if it means that all X variables are related to material supply chain risk, and the regression model obtained is: Ŷ=7.408+0.096X1-0.006.X2+ 0.132X3+0.112X4. From the results of the coefficient of determination, the value of R2 = 14.6%, which means that the risk of the material supply chain is influenced by supply factors, control factors, demand factors, process factors, amounting to 14.6%, the remaining 85.4% is influenced by other factors variables which are not included in this study.